Optical aid for placing composite material (prepregs) in a mould - Schreve, K.; Van der Westhuizen, J. (South African Journal of Industrial Engineering, 2018)
Increased industrial use of composite materials for manufacturing strong lightweight components stimulates endeavours for more efficient assembly methods. This study attempted to find an optimal method to provide optical aid for the placement of pre-impregnated reinforcing fabric (prepregs). A novel approach to optical assistance for the placement of prepregs was designed to be straightforward and affordable. The developed system meets industry standards for accuracy, and provides the solution at a cost many times less than existing solutions. The findings allow companies in the composite material industry to eliminate prepreg layup errors at an affordable price.